Effect of Crosslinking Agent (Zinc Chloride) on the Swelling Ratio and Water Retention Capacity of Polyacrylate and Polyvinyl Alcohol - Saja Kadhim; Awham Hameed; Rashed Rasheed (Journal of Applied Sciences and Nanotechnology, 2022)
In this study, using potassium polyacrylate (KPA), polyvinylalcohol (PVA), and zinc chloride as cross-linking agents, successfully synthesized novel superabsorbent polymers. Different weight ratios of KPA and PVA were used to prepare the polymers using polymerization solution. So, polymers with different weight ratios made from PVA and KPA. Superabsorbent polymers (SAPs) were produced using a simple approach at ambient temperature. By comparing absorption peaks, Fourier transform infrared spectroscopy (FTIR) and UV analysis were utilized to investigate the molecular interactions. The morphology of superabsorbent polymers was investigated by scanning electron microscopy (SEM). According to FT-IR, UV, and SEM results, the superabsorbent polymers (Zn-KPA and Zn-PVA) were prepared successfully. A comparison of Zn-KPA and Zn-PVA SAPs was conducted. The effects of cross-linking on water absorption were investigated. The Zn-PVA superabsorbent polymer has a maximum swelling capacity of 407%, while the swelling ratio of the Zn-KPA was 304%. Thus, these prepared superabsorbent polymers could be used for agricultural applications such as water storage. With increasing zinc chloride content and time, superabsorbent polymers’ swelling capacity has considerably improved.